Please explain each and every step while solving!!
![](https://hi-static.z-dn.net/files/df4/0d1f7af32dde14c325f5dd1f0972c6ed.jpg)
Answers
Step-by-step explanation:
a^(x-1) = bc
a^x/a = bc => a^x = abc
=> a = (abc)^1/x ----(1)
b^(y-1) = ac => b^y/ b = ac
b^y = abc => b = (abc)^1/y ----(2)
c^(z-1) = ab => c^z/ c = ab
=> c^z = abc => c = (abc)^1/z -----(3)
multiply (1) ,(2) and (3) ,we get
abc = (abc)^(1/x + 1/y + 1/z)
here base are equal so it will get cancel to each other ,therefore
1 = 1/x + 1/y + 1/ z
Ans: 1/x + 1/y + 1/z = 1
Answer:
a^(x-1) = bc
a^x/a = bc => a^x = abc
=> a = (abc)^1/x ----(1)
b^(y-1) = ac => b^y/ b = ac
b^y = abc => b = (abc)^1/y ----(2)
c^(z-1) = ab => c^z/ c = ab
=> c^z = abc => c = (abc)^1/z -----(3)
multiply (1) ,(2) and (3) ,we get
abc = (abc)^(1/x + 1/y + 1/z)
here base are equal so it will get cancel to each other ,therefore
1 = 1/x + 1/y + 1/ z
Ans: 1/x + 1/y + 1/z = 1